Effects of Fortified Wheat Bran Arabinoxylan on the Quality of Wheat Malt Beer - Kai Jiang; Yuhong Jin (Foods)
Arabinoxylan, a key non-starch polysaccharide in wheat bran, significantly influences the quality and health benefits of wheat beer. This study aimed to investigate how wheat bran addition (0–20%) affects water-extracted arabinoxylan (WEAX) content and beer quality in 100% wheat malt beer. The study integrated physicochemical analyses (polysaccharide composition, WEAX molecular weight), process parameters (wort filtration time, foam stability), and sensory evaluation to establish structure–function relationships. Results showed that the WEAX content in beer increased from 1.36 mg/mL in pure malt beer (0% bran) to 2.25 mg/mL with 20% bran addition. Bran addition shortened wort filtration time by 20–45%. The molecular weight of WEAX was mainly 2936–7062 Da, enhancing foam expansion (36.18%) and stability (15.54%) due to elevated polymerization and arabinose-to-xylose (A/X) ratios. WEAX fractions (7062–10,134 Da and 859–2936 Da) correlated positively with beer turbidity and viscosity. Sensory analysis identified 15% bran as optimal for balanced quality. These findings demonstrate that bran addition enhances WEAX content, polymerization, and A/X ratios, improving foam performance, reducing filtration time, and optimizing beer quality without altering arabinogalactan, glucan, or mannose polymer content.